Bovine hemoglobin concentration is assayable in blood stored for up to 14 days (Revista de Ciências Agroveterinárias, 2017)
Hemoglobin is a protein present in erythrocytes, used in the transport of respiratory gases. This protein can be measured through laboratory tests, thus it is an important tool in health assessment of domestic animals. The hemoglobin test protocol by cyano-met hemoglobin method describes that its measurement can be made during a period of up to seven days, but the laboratorial routine shows a reduction in the values before this period. The objective of this study was to determine what the actual maximum period to measure hemoglobin levels in cattle is without changes. Nineteen healthy bovine animals were used, males and females, who underwent venous blood collection via jugular puncture. Samples were analyzed by manual colorimetric. Analyses were made every 24 hours during a fourteen days-interval. During this interval the samples were kept under refrigeration. Hemoglobin levels varied from 8.546 to 22.456 g/dL. Compared to baseline, there were no significant changes in hemoglobin concentration during the investigated period of time, indicating that its measurement can be performed after 14 days of storage.
Keywords: Hematology; Methodology; Hematimetric index.